SEASONAL DYNAMICS OF INDICATORS OF METABOLISM AND OXYGEN TRANSPORT SYSTEM OF BLOOD OF ATHLETES-SKIERS OF KHANTY-MANSIYSK - Stepanov A.S.; Gubina A.E.; Koinosov An.P.; Pogonyshev D.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate seasonal changes in the parameters of metabolism, blood oxygen transport system and physical performance of athletes specializing in cross-country skiing and biathlon in the conditions of Khanty-Mansiysk. Methods and structure of the study. The study involved young skiers and biathletes, a total of 21 people, of high sports qualification. The age of the surveyed was 17-21 years. The examination was carried out in two stages - May-June ("Spring"), October-November ("Autumn") and included a laboratory blood test (biochemical and general clinical analysis), determination of physical performance and vital capacity of the lungs, bioimpedance analysis of body composition. Results and conclusions. Data analysis showed statistically significant seasonal differences in a number of indicators: changes in the level of aspartate aminotransferase, total and direct bilirubin, creatinine, cortisol, erythrocyte count, hematocrit, hemoglobin saturation of erythrocytes, the relative value of maximum oxygen consumption, the content of the fat component in the body, body mass index. The revealed shifts in important systems (oxygen transport, endocrine, enzyme) reflect the adaptation of metabolic processes to the action of changing natural and climatic factors and physical loads, and can be used in organizing the training process for athletes from the northern region.